Loss of FoxO in skeletal muscle leads to disrupted muscle metabolism and exacerbates starvation-induced hepatic steatosis - Mamoru Oyabu; Manato Sakaue; Atsushi Kubo; Kiyoshi Yoshioka; Runa Kawaguchi; Haruki Yamamoto; Yuzuka Kinjo; Jungin Kwon; Hiroki Nishi; Daisuke Yamanaka; Tomoki Sato; Daiki Mori; et al. (Proceedings of the National Academy of Sciences, 2026)
Up to a third of the global population is afflicted by metabolic dysfunction-associated steatotic liver disease with excessive triglyceride accumulation in the liver. Prolonged fasting rapidly causes hepatic steatosis via excessive influx of free fatty acids from adipose tissue. However, it is unclear whether skeletal muscle is involved in the etiology of hepatic steatosis during starvation. Here, we demonstrate a critical connection between the liver and skeletal muscle via FoxO transcription factors. During prolonged fasting, hepatic steatosis was exacerbated in skeletal muscle–specific FoxO-deficient mice (mFoxO1,3,4 −/− ) despite preventing skeletal muscle wasting, suggesting that skeletal muscle FoxOs prevent hepatic steatosis during energy deprivation. FoxO deficiency in skeletal muscle weakened fatty acid oxidation and induced abnormal glycogen accumulation in skeletal muscle during fasting. Mechanistically, the starvation-induced transcriptional regulation of triglyceride lipase was attenuated in skeletal muscle of FoxO-deficient mice. Conversely, skeletal muscle–specific FOXO1 overexpression was sufficient to increase triglyceride lipase in vivo and protected the liver from Western diet–induced metabolic dysfunction–associated steatohepatitis-like phenotype. Taken together, our results demonstrate the physiological importance of skeletal muscle FoxO signaling on the liver pathophysiology.